1999
DOI: 10.1007/s002800050971
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/pharmacokinetic trial of the novel thioxanthone SR233377 (WIN33377) on a 5-day schedule

Abstract: We conclude that SR233377 administered on a 5-day schedule is associated with tolerable clinical symptoms and some activity against a range of solid tumors but dosing is limited by QTc prolongation, a condition that predisposes to ventricular arrhythmias. Phase II development on this schedule is not recommended based on the occurrence of this concentration-dependent effect. Further investigation of alternative schedules of administration and of SR233377 analogues is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…8,9 Many of these applications rely on triplet excitation of TX. Several studies, both experimental 10−16 and theoretical, [10][11][12]17 have dealt with the photoinduced processes resulting in the triplet excitation.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Many of these applications rely on triplet excitation of TX. Several studies, both experimental 10−16 and theoretical, [10][11][12]17 have dealt with the photoinduced processes resulting in the triplet excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Thioxanthone (TX) and its derivatives are efficient photosensitizers, which have attracted much attention in recent years owing to their broad spectrum of antitumor activities and great potential to be developed as novel antitumor agents [13]. It has been reported that photoexcited TX can cause DNA damage [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TXs was discovered to have broad spectrum efficacy against solid tumors. Its antitumor activity has attracted more and more interest in recent years and is being developed for a novel drug [7][8][9][10]. K. Hirakawa et al has studied the DNA damage by photo-excited TX.…”
Section: Introductionmentioning
confidence: 99%